Thermodynamic analysis of nutating disc engine topping cycles for aero-engine applications - Sebastiampillai, Joshua; Rolt, Andrew Martin; Jacob, Florian; Nalianda, Devaiah; Sethi, Vishal (Elsevier, 2019)
Within the next thirty years the evolutionary approach to aero engine development will struggle to keep abreast with increasingly stringent environmental targets. Therefore radical approaches to aero-engine development in terms of energy savings need to be considered. One particular concept involves the inclusion of a pressure-rise combustion system, within the architecture of an aero-engine, to provide additional shaft power. The nutating disc engine concept is a strong contender due to its power density. The feasibility of the nutating disc engine has been previously investigated for unmanned vehicle applications. However, this paper investigates the performance benefits of incorporating a nutating disc core in a larger geared open rotor engine for a potential entry in to service in 2050. In addition, a methodology is presented to estimate the size and weight of the nutating disc core. This methodology is pivotal in determining the overall performance of the novel aero-engine cycle. The outcome of this study predicts a potential 9.4% fuel burn benefit, over a state of the art geared open rotor in the year 2050. In addition, the sensitivity of the nutating disc design variables highlights the possible fuel burn benefits compared against a comparable year-2000 aircraft mission.
Keywords: Nutating disc engine; Combined cycle; Fuel burn; Geared open rotor